EGTA Can Inhibit Vesicular Release in the Nanodomain of Single Ca2+ Channels - Nakamura, Yukihiro (Frontiers in Synaptic Neuroscience, 2019)
The exogenous Ca chelator EGTA has been widely used for probing the coupling distance between Ca channels and vesicular Ca sensor for neurotransmitter release. Because of its slow forward on rate, EGTA is thought to not capture Ca ions in the very proximity to a channel, whereas it does capture Ca ions at the remote distance. However, in this study, our reaction diffusion simulations of Ca combined with release calculation using vesicular sensor models indicate that high concentration of EGTA decreased Ca and vesicular release in the nanodomain of single channels. We found that a key determinant of the inhibitory EGTA effect on neurotransmitter release is the saturation of vesicular sensor. When the sensor is saturated, the reduction in Ca by EGTA is masked. In contrast, when the sensor is in a linear range, even a small reduction in Ca by EGTA can decrease vesicular release. At the close proximity of channel, the vesicular sensor is often saturated for a long voltage-step, but not for a brief Ca influx typically evoked by an action potential. Therefore, when EGTA is used as a diagnostic tool to probe the coupling distance, care must be taken for presynaptic Ca entry duration as well as the property of the vesicular sensor.